Gut microbiota and psoriasis: pathogenesis, targeted therapy, and future directions - Zou, Xinyan; Zou, Xinfu; Gao, Longxia; Zhao, Hanqing (Frontiers in Cellular and Infection Microbiology, 2024)
BackgroundPsoriasis is one of the most common autoimmune skin diseases. Increasing evidence shows that alterations in the diversity and function of microbiota can participate in the pathogenesis of psoriasis through various pathways and mechanisms.ObjectiveTo review the connection between microbial changes and psoriasis, how microbial-targeted therapy can be used to treat psoriasis, as well as the potential of prebiotics, probiotics, synbiotics, fecal microbiota transplantation, diet, and Traditional Chinese Medicine as supplementary and adjunctive therapies.MethodsLiterature related to the relationship between psoriasis and gut microbiota was searched in PubMed and CNKI.ResultsAdjunct therapies such as dietary interventions, traditional Chinese medicine, and probiotics can enhance gut microbiota abundance and diversity in patients with psoriasis. These therapies stimulate immune mediators including IL-23, IL-17, IL-22, and modulate gamma interferon (IFN-γ) along with the NF-kB pathway, thereby suppressing the release of pro-inflammatory cytokines and ameliorating systemic inflammatory conditions.ConclusionThis article discusses the direction of future research and clinical treatment of psoriasis from the perspective of intestinal microbiota and the mechanism of traditional Chinese medicine, so as to provide clinicians with more comprehensive diagnosis and treatment options and bring greater hope to patients with psoriasis.